The Influence of Competence and Patient Satisfaction to the Employee Per-formance through Service Quality at Community Health Center in Ternate City - Rabiatul Adawiah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The Influence of Competence and Patient Satisfaction on Employee Performance Through Service Quality at Health Centers in Ternate City. (supervised by Tajuddin Malik and Gunawan Ilyas). This study aims to (1) analyze the influ-ence of competence on service quality at Health Centers in Ternate City; (2) analyze the influence of patient satisfac-tion on service quality at Health Centers in Ternate City; (3) analyze the influence of competence on employee perfor-mance at Health Centers in Ternate City; (4) analyze the influence of patient satisfaction on employee performance at Health Centers in Ternate City; (5) analyze the influence of service quality on employee performance at Health Centers in Ternate City; (6) analyze the influence of competence on employee performance through service quality at Health Centers in Ternate City; (7) analyze the influence of patient satisfaction on employee performance through service quality at Health Centers in Ternate City This study was conducted at 11 Health Centers in Ternate City. The sample used Maximum Likelihood Estimation and proportional random sampling. All samples amounted to 100 respondents at the research location xxx. The data collection method used was direct interviews with the parties involved in the prob-lem being discussed and providing questionnaires to patients in accordance with the research being conducted. Data analysis was carried out using descriptive analysis and path analysis. The results of the analysis showed that (1) compe-tence influenced the quality of service at the Health Center in Ternate City; (2) patient satisfaction influenced the quali-ty of service at the Health Center in Ternate City; (3) competence influenced employee performance at the Health Cen-ter in Ternate City; (4) patient satisfaction influenced employee performance at the Health Center in Ternate City; (5) service quality influenced employee performance at the Health Center in Ternate City; (6) competence influenced em-ployee performance through service quality at the Health Center in Ternate City; (7) patient satisfaction influenced employee performance through service quality at the Health Center in Ternate City